Design of a Display Structure for an Anti-Collision System of Offshore Drilling Units Based on the Digital Twin Concept - Ki-Youn Kwon; Namkug Ku; Jaeyong Lee (Journal of Marine Science and Engineering, 2022)
The drill floor of an offshore drilling facility is equipped with a collision avoidance system to prevent collisions between moving equipment. In this paper, we present the visualization of the collision avoidance system using the digital twin concept. By classifying the core technologies of the digital twin, the elements necessary for the visualization of the collision avoidance system are derived, and the information for visualization is organized. We conduct 3D visualization of equipment and design IO devices necessary for the visualization. The movement of the floater is considered, and a database is built to efficiently search for the information required for the retrieval of stored 3D information. A collision detection situation is generated by operating the equipment using the input device required for simulation. Collision information is displayed as designed, and it is confirmed that the switching of the display between the present and past time is operating normally. The entire system functions normally as designed, including the input/output with other databases and equipment operation. Implementing a digital twin for an offshore platform is a time-consuming and costly process. It is expected that the improved anti-collision system can be expanded for the digital twin of an entire offshore platform.